2018
DOI: 10.1161/circulationaha.117.029254
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Follow-Up Hemodynamic Variables After Initial Management in Pulmonary Arterial Hypertension

Abstract: SVI and right atrial pressure were the hemodynamic variables that were independently associated with death or lung transplantation at first follow-up RHC after initial PAH treatment. These findings suggest that the SVI could be a more appropriate treatment target than cardiac index in PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
170
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(196 citation statements)
references
References 35 publications
21
170
2
3
Order By: Relevance
“…However, in a new study rom the French PAH registry, only a 6MWD ≤440 m independently predicted death or transplantation, whereas baseline WHO/NYHA functional class III-IV, RAP ≥8 mm Hg and cardiac index < 2.5 L × min −1 × m −2 were associated with a higher risk of death or transplantation in the univariate analysis [5]. These and further studies [4][5][6][7] confirmed that haemodynamic variables obtained by right heart catheterization are essential for risk stratification as proposed by the guidelines. On the other hand, in many studies, single haemodynamic variables were not independent prognostic predictors and varied largely in their prognostic relevance within different studies [2,[4][5][6]8].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…However, in a new study rom the French PAH registry, only a 6MWD ≤440 m independently predicted death or transplantation, whereas baseline WHO/NYHA functional class III-IV, RAP ≥8 mm Hg and cardiac index < 2.5 L × min −1 × m −2 were associated with a higher risk of death or transplantation in the univariate analysis [5]. These and further studies [4][5][6][7] confirmed that haemodynamic variables obtained by right heart catheterization are essential for risk stratification as proposed by the guidelines. On the other hand, in many studies, single haemodynamic variables were not independent prognostic predictors and varied largely in their prognostic relevance within different studies [2,[4][5][6]8].…”
Section: Introductionmentioning
confidence: 88%
“…In both cohorts, patients with an RV index > 91 had a significantly increased mortality compared to patients with an RV index ≤91 (p = 0.00092). The fully adjusted Cox regression analysis (model 3) showed a more than 2.5-fold higher mortality risk in patients with an RV index above the cutoff (HR 2.56 [95% CI 1.29, 5.08], p = 0.0071; Fig. 4).…”
Section: Development Of the Rv Index And Application In The Developmementioning
confidence: 99%
See 3 more Smart Citations